2017
DOI: 10.18632/oncotarget.19169
|View full text |Cite
|
Sign up to set email alerts
|

Small molecular floribundiquinone B derived from medicinal plants inhibits acetylcholinesterase activity

Abstract: Being a neurodegenerative disorder, Alzheimer's disease (AD) is the one of the most terrible diseases. And acetylcholinesterase (AChE) is considered as an important target for treating AD. Acetylcholinesterase inhibitors (AChEI) are considered to be one of the effective drugs for the treatment of AD. The aim of this study is to find a novel potential AChEI as a drug for the treatment of AD. In this study, instead of using the synthetic compounds, we used those extracted from plants to investigate the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 107 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…In the presence of floribundiquinone B, isolated from the roots of Berchemia , CD transitions were observed from α helix to β turn, and random coil and β folds were significantly decreased. In addition to above mentioned studies in fluorescence study it was observed that, dose dependent quenching of intensity of AChE as a function of floribundiquinone B concentration was determined [60]. Also, the interaction of berberine with AChE was examined by fluorescence and CD studies to check the conformational and tertiary structure changes in the enzyme [61].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of floribundiquinone B, isolated from the roots of Berchemia , CD transitions were observed from α helix to β turn, and random coil and β folds were significantly decreased. In addition to above mentioned studies in fluorescence study it was observed that, dose dependent quenching of intensity of AChE as a function of floribundiquinone B concentration was determined [60]. Also, the interaction of berberine with AChE was examined by fluorescence and CD studies to check the conformational and tertiary structure changes in the enzyme [61].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Chou's 5-step rule [32] that has been widely used by many recent investigators (see, e.g., [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]) for developing a statistical predictor, the first important and foremost thing is to construct or select a valid benchmark dataset to train and test the model [1,42,48]. In literature, the benchmark dataset usually consists of a training dataset and a testing dataset: the former is for the purpose of training a proposed model, while the latter for the purpose of testing it.…”
Section: Benchmark Datasetmentioning
confidence: 99%
“…3A, there were two characteristic uorescence peaks upon excitation at 230 nm and 280 nm. The luminescence at the excitation at 230 nm resulted from the structure of the protein polypeptide chain, 22 while that at the excitation at 280 nm resulted from spontaneous uorescence amino acid residues, tyrosine, tryptophan, and phenylalanine. 23 However, cochinchinenin C has very weak uorescence in solution.…”
Section: The Interaction Between Cochinchinenin C and Glp1 Receptormentioning
confidence: 99%